Exploring Indonesia-Paraguay trade potentials:A revealed comparative advantage approach - Sulthon Sjahril Sabaruddin; Sihar Tambun (Proceedings of AICS - Social Sciences, 2013)
This paper attempts to identify and analyze the Indonesia-Paraguay bilateral trade potentials based on their respective export competitiveness. The analysis uses the Revealed Comparative Advantage Index for year 2012 obtained from World Integrated Trade Solution (WITS). The paper reveals that there are huge opportunities for both countries to further strengthen bilateral trade relations.Based on the RCA Index analysis, the paper revealed that in general both countrieshave exported their commodities based on theirrespective comparative advantages, but however both countries current exports still do not reflect their potentials as most for Indonesia (none for Paraguay) of the top ten commodities with the strongest comparative advantagewereunable to penetrate both sides market. This study suggests both countries should remove trade barriers starting by providing access for the top 10 export commodities with the strongest comparative advantage to penetrate in both countries. This step could be a stepping stone towards strengthening bilateral trade relations.Keywords: Comparative Advantage, Export Competitiveness, Bilateral Trade Relation JEL classification numbers: F14, F15, F17